2012
DOI: 10.1021/jm201441k
|View full text |Cite
|
Sign up to set email alerts
|

Fragment Based Drug Discovery: Practical Implementation Based on 19F NMR Spectroscopy

Abstract: Fragment based drug discovery (FBDD) is a widely used tool for discovering novel therapeutics. NMR is a powerful means for implementing FBDD, and several approaches have been proposed utilizing (1)H-(15)N heteronuclear single quantum coherence (HSQC) as well as one-dimensional (1)H and (19)F NMR to screen compound mixtures against a target of interest. While proton-based NMR methods of fragment screening (FBS) have been well documented and are widely used, the use of (19)F detection in FBS has been only recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 45 publications
3
92
0
Order By: Relevance
“…The same group also described an interesting variant of these screening approaches in which the enzymatic conversion of a fluorine-containing substrate to product was monitored by 19 F-NMR; this was exemplified with the membrane-bound enzyme fatty acid amide hydrolase, using a library of fluorinated fragments to inhibit the enzymatic conversion [20]. Jordan and co-workers at Amgen (Thousand Oaks, CA, USA) have also evaluated 19 F-NMR-based fragment screening and shown that it is not only a rapid and sensitive method for detecting fragment hits, but can also contribute to the development of structure-activity relationships (SAR) on the hit-to-lead path and provide an efficient means of assessing target druggability [21]. They also noted that the large chemical shift dispersion and narrow linewidth (1-2 Hz in the presence of proton decoupling, although we note that proton decoupling is often not used) for 19 F resonances of the free ligands enable the screening of a large number of compounds in a cocktail without the complication of signal overlap.…”
Section: Screening Fragment Librariesmentioning
confidence: 99%
See 1 more Smart Citation
“…The same group also described an interesting variant of these screening approaches in which the enzymatic conversion of a fluorine-containing substrate to product was monitored by 19 F-NMR; this was exemplified with the membrane-bound enzyme fatty acid amide hydrolase, using a library of fluorinated fragments to inhibit the enzymatic conversion [20]. Jordan and co-workers at Amgen (Thousand Oaks, CA, USA) have also evaluated 19 F-NMR-based fragment screening and shown that it is not only a rapid and sensitive method for detecting fragment hits, but can also contribute to the development of structure-activity relationships (SAR) on the hit-to-lead path and provide an efficient means of assessing target druggability [21]. They also noted that the large chemical shift dispersion and narrow linewidth (1-2 Hz in the presence of proton decoupling, although we note that proton decoupling is often not used) for 19 F resonances of the free ligands enable the screening of a large number of compounds in a cocktail without the complication of signal overlap.…”
Section: Screening Fragment Librariesmentioning
confidence: 99%
“…This leads to the idea that the binding site of a fluorine-containing elaborated fragment on a target protein could be 'mapped' by creating a series of fluorine-containing ligands that would be expected to bind in the same way, and then monitoring the magnitude of the chemical shift change upon binding. Systematic fluorine substitution around an aromatic ring, for example, could be undertaken to establish which positions are most perturbed by protein binding [18,21]. Figure S4).…”
Section: Ligand Binding Site Mappingmentioning
confidence: 99%
“…In a recent example of NMR screening against fluorinated fragment library, 12 ~ 13 fragments were combined together into each cocktail 11 and more than 1,000 fragments can be screened within 24 hours, demonstrating fluorine NMR can be another attractive tool in FBDD. In the light of my experience, if well designed, 40 ~ 100 19 F-fragments mixture can be seemingly screened at a time without solubility and DMSO tolerance issues because the 19 F-fragments have very simple resonances and their dynamic range of resonances is wider than that of proton by more than 20-fold.…”
Section: Nmr In Fbddmentioning
confidence: 99%
“…Quality control for non plate-based fragment screening methods is not as standardized yet as for conventional in vitro assays, still, Congreve et al included regularly a positive control at SPR testing to demonstrate reproducibility and stability of the assay (12). Lately, independently from 1 H techniques, 19 F NMR has been proposed as an efficient tool for fragment screening based on its high sensitivity and specificity suitable for screening mixtures (66). In theory, combination of TINS with 19 F NMR spectroscopy could yield a method of improved throughput and detection sensitivity to be applied for screening reasonable size fragment libraries against GPCRs and other membrane targets.…”
Section: Expert Opinionmentioning
confidence: 99%